Economic advice and executive policy - "Sichel, Werner (ed.)" (New York, 1978)
The essays included in this book were originally prepared for presentation in the Seminar in Economics series at Western Michigan University during the 1976-77 academic year.
Keywords: United Srtates - economic policy -1945 -1960